DIMENSI RUBUBIYAH DALAM PENCIPTAAN ALAM PERSPEKTIF AL-QUR’AN: PROMOSI EKOTEOLOGI DALAM KONSERVASI LINGKUNGAN - Tamam, Badru; Hude, Darwis; Anwar, Hamdani; Kholilurrohman, Kholilurrohman; Febriani, Nur Arfiyah (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
Stephen Hawking, a realist who adheres to positivism, asserts that the universe was created without God. This perspective considers nature to be only matter, an entity without a soul. On the other hand, one of the factors causing environmental damage is the anthropocentric paradigm that considers humans as the most important element in the universe. Ironically, this paradigm uses the holy book of the heavenly religions to legitimize its thinking, as found in Genesis 1:28 and the Qur'an in Surah al-Baqarah [2]: 29. In the interpretation of the Qur'an, to find a concept is not enough with just one verse, a series of steps need to be taken in order to produce a comprehensive interpretation. For this reason, the Maudu'i interpretation method is used to explore the concept of the Qur'an about the creation of the universe and its maintenance and how humans function in the universe. The authors found that: 1. With the Rububiyah dimension, Allah SWT is the Creator, Owner, Manager and Maintainer of nature. Humans are the khalifatullah/representatives of Allah SWT on earth who are allowed to use natural resources while maintaining their sustainability. 2. Ecotheology in the Qur'an can be understood in the sense: "The science that studies the interaction between creatures in their ecosystem based on the verses of takwn (universe/ecology) and tadwn (Qur'anic texts as the basis of theology)." Ecotheology is related to efforts to preserve the environment through balancing human rights and obligations towards nature and respect for the human rights of nature. This is because in the Qur'an, both humans and nature have their respective roles and purposes of creation as fellow creations of God. Humans as khalifah fi al-‘ard}/prosperers of the earth and nature are partners of humans in carrying out this mandate. Nature is the same as humans as fellow creations of God (ukhuwah makhluqiyyah) who also have the right to worship, develop and live in groups in their communities